An accelerated variant of the projection based parallel hybrid algorithm for split null point problems - Arfat, Yasir; Kumam, Poom; Khan, Muhammad Aqeel Ahmad; Ngiamsunthorn, Parinya Sa (Topological Methods in Nonlinear Analysis, 2022)
In this paper, we consider an accelerated shrinking projection based parallel hybrid algorithm to study the split null point problem (SNPP) associated with the maximal monotone operators in Hilbert spaces. The analysis of the proposed algorithm provides strong convergence results under suitable set of control conditions as well as viability with the help of a numerical experiment. The results presented in this paper improve various existing results in the current literature.